A Pagan Landscape: Pope Pius XI, Fascism, and the Struggle over the Roman Cityscape - Baxa, Paul (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractThis article examines the two visions of Rome put forward by Fascist dictator Benito Mussolini and Pope Pius XI and the tensions they caused. The rivalry between the two men over the meaning of the Roman landscape became sharper in the 1930s when the Fascist regime transformed the Eternal City through extensive demolition and increasing archaeological activity in the city. Pius XI increasingly viewed these activities as an attempt to “paganize” Rome. The Pope’s fears over paganism came to a head in the days of Adolf Hitler’s famous visit to Italy in May 1938. The development of closer relations between Fascist Italy and Nazi Germany made Pius XI increasingly concerned about what he called the “neo-pagan” nature of these ideologies. Ultimately, the cityscape of Rome was transformed into a kulturkampf between Fascism and the Vatican which not only gives us a fuller picture of the seemingly cordial relations between Pius and Mussolini in the 1930s, but also reveals Fascism as a political religion inevitably in conflict with the other religion, Catholicism, which saw Rome as its own.